RANCANG BANGUN SISTEM INFORMASI MATERIAL BANGUNAN MENGGUNAKAN METODE UCD (USER CENTER DESIGN) STUDI KASUS UD. ABANG ADIK RANTAUPRAPAT - Dinda Barianti Sinaga; Muhammad Bobbi Kurniawan Nasution; Shabrina Rasyid Munthe (LPPM Universitas Al Washliyah Labuhanbatu, 2021)
UD Building Shop. Abang Adik Rantauprapat is a business that is engaged in the sale of building goods. Transactions are still recorded manually in the form of notes, data processing and reporting often experience data inaccuracies and delays in delivering data information. From the results of research conducted, the researcher intends to solve the problems faced at UD. Rantauprapat's brother. Therefore, an information system design is needed. In developing the system used in the manufacture of this goods sales application using a structured approach, namely the user centered design (UCD) method where the data collection techniques used include a methodology consisting of 3 basic processes, namely analysis, design, and evaluation consisting of survey methods , task analysis, persona, product backlog, design guidelines, prototypes, user testing, and heuristic evaluations. The development method uses a structured method with several tools and techniques such as context diagrams and data flow diagrams. The programming language used in designing and implementing sales information systems is PHP MySQL. The results of research at UD.